Structural Basis for Hemophilia A Caused by Mutations in the C Domains of Blood Coagulation Factor VIII - Gale, Andrew J.; Pellequer, Jean-Luc; Getzoff, Elizabeth D.; Griffin, John H. (Thrombosis and Haemostasis, 2000)
Three dimensional homology models for the C1 and C2 domains of factor VIII (FVIII) were generated. Each C domain formed a β-sandwich, and C1 was covalently connected to C2 in a head-to-head orientation. Of the >250 missense mutations that cause FVIII deficiency and hemophilia A, 34 are in the C domains. We used the FVIII C1-C2 model to infer the structural basis for the pathologic effects of these mutations. The mutated residues were divided into four categories: 15 conserved buried residues that affect normal packing of the hydrophobic side chains, 2 non-conserved buried residues that affect structure, 11 conserved exposed residues and 6 non-conserved exposed residues. The effects of all 34 missense mutations can be rationalized by predictable disruptions of FVIII structure while at most four mutations (S2069F, T2154I, R2209Q/G/L and E2181D) may affect residues directly involved in intermolecular interactions of FVIII/VIIIa with other coagulation factors or vWF.
Keywords: Hemophilia A; Factor VIII; homology modeling; von Willebrand factor; coagulation